Psychotrauma after occupational accidents in public transportation. A pilot study to support concepts, influencing factors and occupational health-care - Clarner, Annika; Krahl, J.; Uter, Wolfgang; Drexler, Hans; Martin, A. (Gesundheitswesen, 2015)
Accidents, assaults and suicides occur quite frequently in public transportation. As a result of such extreme events at work, drivers are particularly prone to psychotrauma (PT). Therefore accident insurers stipulate support from the accident site to workplace reintegration with the inclusion of occupational medicine. The present study investigates the incidence, factors influencing psychological trauma as well as the occupational health-care after critical incidents.In a Bavarian public transportation corporation 59 employees were evaluated according to ICD-10 for trauma-related disorders, using full collection after application of a specific mental first aid programme and a subsequent occupational health examination.The incidence of PT was 44.1%, with 8.5% showing a post-traumatic stress disorder (PTSD) as consequence of the accident. As significant influencing factors the nature of the accident, the severity of third party injury, and own physical injuries were identified. The occupational medical care depended on the severity of the disease. PT led to the need for rehabilitation. Sick leave was most pronounced in drivers with PTSD.The study group showed high levels of emotional strain within the first month. With respect to occupational health-care, particular attention should be paid to drivers after serious accidents or those who sustained own injuries. As foundation for evidence based health-care measures after PT in transport must be scientifically evaluated and the identified risk factors must be well-founded as well.
EVALuna2:5522